CATTLE PYROPLASMOSIS THERAPY AND PREVENTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article states that uzbicarb effectiveness in the pyroplasia treatment in cattle is higher than 3 mg/kg cattles live weight, and the polycarb prophylactic effect in 5.0 ml per 100 kg of live weight is 15 days.